(untitled) (Global Journal of Human-Social Science, 2014)
The worship mode of Africans is often enriched by songs that contain expressions of their faith, recount stories or render praise to God. They have taken pleasure and given regard to composing these songs in their local dialect, thus communicating the essence of Bible messages in ways that English language could not have been able to do. These songs have done much in Church teaching, indicating that mother tongue is a key factor in communicating to a larger audience in Kwambai community. Though English language was the original medium through which Christianity was propagated among them, the people have adopted and modified the gospel message to suit their needs. The assessment in this study relied on observation and unstructured interviews with song composers and other members of the community. The study opines that the role of mother tongue in communication cannot be underplayed if people in local communities will be reached with the message of the Gospel.